Effect of Low-Input Organic and Conventional Farming Systems on Maize Rhizosphere in Two Portuguese Open-Pollinated Varieties (OPV), “Pigarro” (Improved Landrace) and “SinPre” (a Composite Cross Population) - Ares, Aitana; Costa, Joana; Joaquim, Carolina; Pintado, Duarte; Santos, Daniela; Messmer, Monika M.; Mendes-Moreira, Pedro M. (Frontiers in Microbiology, 2021)
Maize is one of the most important crops worldwide and is the number one arable crop in Portugal. A transition from the conventional farming system to organic agriculture requires optimization of cultivars and management, being the interaction plant-soil rhizosphere microbiota pivotal. The objectives of this study were to unravel the effect of population genotype and farming system on microbial communities in the rhizosphere of maize. Rhizosphere soil samples of two open-pollinated maize populations ('SinPre' and 'Pigarro') cultivated under conventional and organic farming systems were taken during flowering and analysed by NGS. Phenological data was collected from the replicated field trial. A total of 266 fungi and 317 bacteria genera were identified in 'SinPre' and 'Pigarro' populations of which 186 (69.9%) and 277 (87.4%) were shared among them. The microbiota of 'Pigarro' showed a significant higher (P < 0.05) average abundance than the microbiota of 'SinPre'.The farming system had a statistically significant impact (P < 0.05) on the soil rhizosphere microbiota and several fungal and bacterial taxa were found to be farming-system specific. The rhizosphere microbiota diversity in the organic farming system was higher than in the conventional for both varieties. The presence of arbuscular mycorrhizae (Glomeromycota)was mainly detected in the microbiota of 'SinPre' population under organic farming systems and very rare under conventional systems. A detailed metagenome function prediction was performed. At the fungal level, pathotroph-saprotroph and pathotroph-symbiotroph lifestyles were modified by the farming system. For bacterial microbiota, the main functions altered by the farming system were membrane transport, transcription, translation, cell motility and signal transduction. This study allowed to identify groups of microorganisms known for their role as plant-growth-promoting rhizobacteria (PGPR) and with the capacity to improve crop tolerance for stress conditions allowing to minimize the use of synthetic fertilizers and pesticides. Arbuscular mycorrhizas (phyla Glomeromycota) were among the most important functional groups in the fungal microbiota and Achromobacter, Burkholderia, Erwinia, Lysinibacillus, Paenibacillus, Pseudomonas and Stenotrophomonasin the bacterial microbiota. In this perspective, the potential role of these microorganisms will be explored in future research.